Characterization of the Rate and Temperature Sensitivities of Bacterial Remineralization of Dissolved Organic Phosphorus Compounds by Natural Populations - White, Angelicque E.; Watkins-Brandt, Katie; Engle, Morgan; Burkhardt, Brian; Paytan, Adina (Frontiers in Microbiology, 2012)
Production, transformation, and degradation are the principal components of the cycling of dissolved organic matter (DOM) in marine systems. Heterotrophic Bacteria (and Archaea) play a large part in this cycling via enzymatic decomposition and intracellular transformations of organic material to inorganic carbon (C), nitrogen (N) , and phosphorus (P). The rate and magnitude of inorganic nutrient regeneration from DOM is related to the elemental composition and lability of DOM substrates as well as the nutritional needs of the mediating organisms. While many previous efforts have focused on C and N cycling of DOM, less is known in regards to the controls of organic P utilization and remineralization by natural populations of bacteria. In order to constrain the relative time scales and degradation of select dissolved organic P (DOP) compounds we have conducted a series of experiments focused on (1) assessment of the short-term lability of a range of DOP compounds, (2) characterization of labile DOP remineralization rates and (3) examination of temperature sensitivities of labile DOP remineralization for varying bacterial populations. Results reinforce previous findings of monoester and polyphosphate lability and the relative recalcitrance of a model phosphonate: 2-aminoethylphosphonate. High resolution time-series of P monoester remineralization indicates decay constants on the order of 0.67-7.04 d-1 for bacterial populations isolated from coastal and open ocean surface waters. The variability of these rates is predictably related to incubation temperature and initial concentrations of heterotrophic bacteria. Additional controls on DOP hydrolysis included seasonal shifts in bacterial populations and the physiological state of bacteria at the initiation of DOP addition experiments. Composite results indicate that bacterial hydrolysis of P-monoesters exceeds bacterial P demand and thus DOP remineralization efficiency may control P availability to autotrophs.